2022
DOI: 10.1111/imcb.12613
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T‐cell stability and functional plasticity in health and disease

Abstract: FOXP3-expressing regulatory T cells (T reg ) are indispensable for immune homeostasis and tolerance, and in addition tissue-resident T reg have been found to perform noncanonical, tissue-specific functions. For optimal tolerogenic function during inflammatory disease, T reg are equipped with mechanisms that assure lineage stability. T reg lineage stability is closely linked to the installation and maintenance of a lineage-specific epigenetic landscape, specifically a T regspecific DNA demethylation pattern. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 197 publications
(484 reference statements)
2
5
0
2
Order By: Relevance
“…Other examples for which, to our knowledge, no IRF4 heterodimer binding was demonstrated before are EP300, FLI1 and TCF7. In our dataset, we found an IRF4-EP300 steered regulation of Th17 and iTreg effector functions supporting data from previous studies, which reported a role of EP300 in Treg proliferation and suppressive function as well as FOXP3 stability 75,76 . In case of Th17 cells, EP300 is essential for the expression of pro-inflammatory cytokines and Th17 cell fate 77 .…”
Section: Discussionsupporting
confidence: 91%
“…Other examples for which, to our knowledge, no IRF4 heterodimer binding was demonstrated before are EP300, FLI1 and TCF7. In our dataset, we found an IRF4-EP300 steered regulation of Th17 and iTreg effector functions supporting data from previous studies, which reported a role of EP300 in Treg proliferation and suppressive function as well as FOXP3 stability 75,76 . In case of Th17 cells, EP300 is essential for the expression of pro-inflammatory cytokines and Th17 cell fate 77 .…”
Section: Discussionsupporting
confidence: 91%
“…Studies have reported plasticity in Treg phenotypes, where their immunosuppressive activity is lost and they produce pro-inflammatory cytokines. 202 Similar phenomena appear in the FBR literature. In a volumetric muscle loss (VML) model, CD3 + T cells were isolated and sequenced from the inguinal lymph nodes that drain the injury site.…”
Section: The Role Of T Cells In the Development Of The Fbrsupporting
confidence: 72%
“…Additionally, others have reported that Treg are increased in the stroma in high-grade disease [ 34 ]. CD4+FoxP3+ cells demonstrate functional plasticity [ 35 ]. We note that CD4+FoxP3+ cells were detected at a low frequency in the lesional tissue (around 10-fold less than the CD8 T cells), and it is unclear what functional impact this comparatively low number of cells may have.…”
Section: Discussionmentioning
confidence: 99%
“…Types included in the alpha genera are of particular interest because of their association with cancer. Thirteen HPV types within the α5 (type 51), α6 (type 56 and 66), α7 (type 18, 45, 39, and 59), and α9 (type 16,31,33,35,52, and 58) species are classified by the International Approval and Registration Centre (IARC) as Group 1 carcinogens (sufficient evidence for carcinogenicity in humans) [1].…”
Section: Introductionmentioning
confidence: 99%